Clinical Arterial Peripheral Vascular Pathology Does Not Impact Short- or Long-Term Survival after Transcatheter Aortic Valve Replacement - Brent Klinkhammer (International Journal of Vascular Medicine)
Introduction. The dramatic changes in vascular hemodynamics after transcatheter aortic valve replacement (TAVR) are well noted. However, little postprocedural data exists on the outcomes in patients with clinical arterial peripheral vascular pathology [abdominal aortic aneurysm (AAA), carotid artery stenosis (CAS), and peripheral artery disease (PAD)] undergoing TAVR for severe aortic stenosis. Setting. A single center healthcare system. Methodology. A retrospective chart review case-control study of 342 consecutive patients who underwent a TAVR for severe aortic stenosis at Sanford Health in Fargo; ND was performed to determine if preprocedural comorbid AAA, CAS, or PAD was associated with worse outcomes after TAVR. Results. Patients with preprocedural comorbid AAA, CAS, or PAD had no significant difference overall survival at 1 month (94% versus 95% p =.812), 6 months (88% versus 89% p = .847), 1 year (74% versus 83%, p =.130), or 2 years (58% versus 63%, p =.611) after TAVR. Patients with clinical arterial peripheral vascular pathology also had no significant difference in preprocedural outcomes. Conclusion. This study gives evidence to suggest that patients with a comorbid clinical peripheral arterial pathology at the time of TAVR do not have a statistically significant increase in mortality out to 2 years after TAVR and no increase in procedural complications. These results affirm the safety and feasibility of TAVR in patients with AAA, CAS, and/or PAD.